Optical properties of ZrO2, SiO2 and TiO2-SiO2 xerogels and coatings doped with Eu3+ and Eu2+ - Gonçalves, Rogéria R. [UNESP]; Messaddeq, Younes [UNESP]; Atik, Mohamed [UNESP]; Ribeiro, Sidney J.l. [UNESP] (ABM, ABC, ABPol, 1999)
Eu3+ doped bulk monoliths and thin films were obtained by sol-gel methods in the ZrO2, SiO2 and SiO2-TiO2 systems. Eu3+ 5D0 ® 7FJ emission and decay time characteristics were measured during the entire experimental preparation route from the initial sol to the final xerogels. The crystalline phases identified were tetragonal ZrO2 and mixtures of rutile and anatase TiO2 at high temperature treatments in bulk samples. Good quality thin films were obtained for all systems by dip-coating optical glasses (Schott BK270). The same spectroscopic features were observed either for the bulk monoliths or the films. By appropriate heat treatments under H2 atmosphere Eu2+ containing samples could be obtained in the SiO2-TiO2 system.
Keywords: rare earths; Eu3+ spectroscopy; silica; titania; zirconia; thin films